A preliminary study on local administration of dexamethasone after tooth extraction ─ Better preservation of residual alveolar ridge? - Poštić, Srdjan D.; Todorović, Ljubomir (Vojnosanitetski pregled, 2014)
Background/Aim. It is important that the height of the edentulous alveolar ridge after tooth extraction remains at a reasonable acceptable level for as long as possible. The aim of this study was to report preliminary results of the clinical effect of local oral submucous administration of dexamethasone after tooth extractions in order to prepare alveolar supporting tissues for acceptance of removable dentures. Methods. In a total of 15 patients (11 partially and 4 completely edentulous) the quantity of 0.25 mL to 0.5 mL of dexamethasone was injected bucally and orally in the region of the tooth socket after complicated extractions. Results. Healing of extraction wounds was uneventful in all the patients, without pain or local inflammation. Conclusion. Dexamethasone can be locally applied to oral tissues to prevent post-extraction inflammation and extensive resorption of the residual alveolar ridge. The obtained results are promising for patients undergoing classic prosthodontic rehabilitation soon after tooth extraction, demonstrating that there are no adverse effects after local oral corticosteroids administration.
Keywords: oral surgical procedures; preprosthetic; tooth extraction; alveolar process; rehabilitation; dexamethasone; treatment outcome